2005
DOI: 10.1542/peds.2004-2012
|View full text |Cite
|
Sign up to set email alerts
|

Coarse Particulate Matter and Hospitalization for Respiratory Infections in Children Younger Than 15 Years in Toronto: A Case-Crossover Analysis

Abstract: ABSTRACT. Objectives. The purpose of this study was to examine the association between ambient air pollution and hospitalization for respiratory infections among children who were younger than 15 years in Toronto during a 4-year period (1998 -2001).Methods. Exposures averaged during periods that varied from 1 to 7 days were used to assess the effects of air pollutants, including thoracic particulate matter (PM 10 ), fine (PM 2.5 ) and coarse (PM 10 -2.5 ) particulate matter, carbon monoxide (CO), sulfur dioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
77
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 34 publications
(58 reference statements)
12
77
2
2
Order By: Relevance
“…Thus, those concentrations of pollutant are associated with the children's hospital admissions due to bronchiolitis, pneumonia, asthma, and bronchitis and other causes. Therefore, this study is consistent with the results shown in other similar works that relate child hospital admissions to PM 2.5 (e.g., Dockery et al, 1989;Lin et al, 2005;Schwartz and Neas, 2000). It is also in line with the results shown in studies that relate this pollutant to cases of pneumonia (Ilabaca et al, 1999) and bronchitis (Barnett et al, 2005), and also with those that relate hospital emergencies due to chronic obstructive pulmonary disease and asthma (Katsouyanni, 2001).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, those concentrations of pollutant are associated with the children's hospital admissions due to bronchiolitis, pneumonia, asthma, and bronchitis and other causes. Therefore, this study is consistent with the results shown in other similar works that relate child hospital admissions to PM 2.5 (e.g., Dockery et al, 1989;Lin et al, 2005;Schwartz and Neas, 2000). It is also in line with the results shown in studies that relate this pollutant to cases of pneumonia (Ilabaca et al, 1999) and bronchitis (Barnett et al, 2005), and also with those that relate hospital emergencies due to chronic obstructive pulmonary disease and asthma (Katsouyanni, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…They analyzed the emergency hospital admissions of children due to all causes, except trauma, in Madrid and found that the only primary pollutant statistically significant was the PM 2.5 concentration, and the relative risk associated with an increase of 10 μg/m 3 in PM 2.5 concentration was 1.03 for children less than 10 years old. In other countries, the impact of fine particle on children health, and specifically on children's respiratory health, has been analyzed by Dockery et al (1989), Lin et al (2005), Schwartz and Neas (2000), Ilabaca et al (1999), Barnett et al (2005), and Magas et al (2007). These latter papers led to the conclusions that first, the results provide further evidence that the rates of respiratory illnesses and symptoms are elevated among children living in cities with high particulate pollution (particularly fine particulates).…”
Section: Introductionmentioning
confidence: 99%
“…Possible links between air pollution, particularly that caused by atmospheric particles and SO 2 , and the number of hospital admissions have been recently established in studies from North America, [3][4][5][6][7][8][9][10][11][12] South America, [13][14][15][16] Asia, [17][18][19][20][21][22] Australia 22 and Europe. [23][24][25][26][27][28][29][30][31][32][33][34][35] However, there are still many aspects to elucidate the causal relationships between air pollution and physical condition, such as the separation of the short-term and long-term health effects of individual air pollutants and those of complex pollutant mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Seniors typically have higher ER visits for CVD, which leads to a higher susceptibility to PM2.5. Other research [17] has supported this fact by showing that those under the age of 65 are less likely than their older counterparts to be hospitalized for CVDs during PM2.5 exposure. Women might be more susceptible because of hormones, but research on the interaction between sex and air pollution has not yet proved such a thing [31].…”
Section: Discussionmentioning
confidence: 89%
“…Previous environmentally epidemiological studies have shown positive correlations of particulate matter (PM) on the risk of death [4][5][6][7][8][9], hospitalizations [3,[10][11][12][13][14][15][16][17], and emergency room 2 of 4 (ER) visits [8,[18][19][20][21]. In Barcelona, Spain, a case-crossover study from 2003 to 2007 indicated that PM2.5 from car exhaust, gas combustion, hyponitrites, hydrosulfites, and road dust are correlated to CVD mortality (p<0.05); for every 10µg/m 3 increase in PM2.5, cardiovascular-related mortality increased by 2.9% (95% CI: 1.4-4.4) [9].…”
Section: Introductionmentioning
confidence: 99%